2020
DOI: 10.1007/s10815-019-01647-y
|View full text |Cite
|
Sign up to set email alerts
|

Thoughts on the ethics of gestational surrogacy: perspectives from religions, Western liberalism, and comparisons with adoption

Abstract: Background In gestational surrogacy, a woman incubates an embryo to which she is not genetically related. Genetic distance from both her and the commissioning parents is increased further when donor gametes are employed. Ethical implications vary depending on the extent to which the parents and surrogates share genetic material with the produced child. Purpose This paper seeks to address two primary questions: What do selected ethical frameworks tell us of (1) the relationship between genetic motherhood, gesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…The opinions concerning surrogacy within Christians are diverse, even though they are, in general, in disfavor of this technique. 185 Hindus regard infertility as a curse, which means they accept ART and surrogacy as a cure for infertility. 185 Regarding Buddhism, since there are few theories written about ART, as long as pain and harm are avoided, all practices are acceptable.…”
Section: Ethical Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…The opinions concerning surrogacy within Christians are diverse, even though they are, in general, in disfavor of this technique. 185 Hindus regard infertility as a curse, which means they accept ART and surrogacy as a cure for infertility. 185 Regarding Buddhism, since there are few theories written about ART, as long as pain and harm are avoided, all practices are acceptable.…”
Section: Ethical Issuesmentioning
confidence: 99%
“…As so, the matter of surrogacy is conflicting. 185 Studies report a duality of criteria in high income countries regarding public opinion about surrogacy. Poll-based studies in Australia, France, Germany, Japan, Philippines, Spain and the USA revealed that more than half of general population would be in favor of surrogate treatments for heterosexual and same-sex couples.…”
Section: Ethical Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Actualmente, esta técnica es un fenómeno comercial global, existiendo diversas agencias encargadas de su desarrollo. [4] Para efectos de comparar los usos, aplicaciones e implicaciones bioéticas entre la maternidad subrogada y la ectogénesis, realizamos una revisión bibliográfica de un total de 39 artículos con fecha de publicación restringida a los últimos 5 años.…”
Section: Procreación Natural Versus Ectogénesisunclassified
“…It must anticipate and address future issues that the couple might encounter, and that requires up-to-date authoritative information. Those relying on the recent conclusion in these pages [1] that Judaism grants maternity to the woman in whose womb the fetus gestates may find the Jewish status of their children is not fully accepted, and they are therefore unable to freely marry within the traditional Jewish community.…”
Section: To the Editormentioning
confidence: 99%